2021
DOI: 10.1177/10690727211050898
|View full text |Cite
|
Sign up to set email alerts
|

Service Workers’ Well-Being During COVID-19: A Strengths-Based Inclusive Theory of Work Perspective

Abstract: This study tested the Strengths-Based Inclusive Theory of Work (S-BIT of Work), a vocational theory that emphasizes positive psychological and cultural factors, among a sample of service industry workers during COVID-19. Service industry workers ( N = 320) were recruited via social media sources across the United States, and structural equation modeling was used to examine the model. This model included privilege and COVID-19 impact as contextual variables; organizational support and workplace dignity as promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…As for negative affects, similarly, the study by Owens et al (2022) found a moderate magnitude correlation coefficient between optimism and stress, confirming the findings of the current study. According to Çutuk (2021), optimism positively affects the SWB because it acts as a shield that calms and mitigates negative experiences, allowing for a change in mood and favoring productive behaviors even in stressful situations making people seek stimuli for solving their problems.…”
Section: Discussionsupporting
confidence: 90%
“…As for negative affects, similarly, the study by Owens et al (2022) found a moderate magnitude correlation coefficient between optimism and stress, confirming the findings of the current study. According to Çutuk (2021), optimism positively affects the SWB because it acts as a shield that calms and mitigates negative experiences, allowing for a change in mood and favoring productive behaviors even in stressful situations making people seek stimuli for solving their problems.…”
Section: Discussionsupporting
confidence: 90%
“…WPD positively predicts discretionary work effort by improving organization-based selfesteem (Ahmed et al, 2021). When employees experience high WPD, their positive individual If I feel valued, I am committed to change characteristics, such as adaptability and empowerment, flourish (Owens et al, 2022), leading to greater fulfilment of employees' social contribution, autonomy and competence needs (Allan and Blustein, 2022). As continuous changes in organizational reality occur, it is pertinent to examine the role of WPD in driving ACC.…”
mentioning
confidence: 99%